Tests and proofs 5th International Conference, TAP 2011, Zurich, Switzerland, June 30 - July 1, 2011 : proceedings - Gogolla, Martin 1954-; Wolff, Burkhart 1962- (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Test and Proofs, TAP 2011, held in Zurich, Switzerland in June/July 2011. The 12 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 27 submissions. Among the topics covered are model checking, testing systems, test generation, symbolic testing, SAT solvers, SMT solvers, property-based testing, automated test generation, learning based testing, UML, OCL, specification-based testing, and network testing.